2021
DOI: 10.1002/aic.17151
|View full text |Cite
|
Sign up to set email alerts
|

In silico mechanically mediated atom transfer radical polymerization: A detailed kinetic study

Abstract: Mechanically mediated atom transfer radical polymerization (mechanoATRP) utilizing ultrasound to generate activators and improve the diffusivity of macromolecular chains is introduced as an innovative externally controlled ATRP. Herein, a comprehensive kinetic model with free volume theory based “series” encounter pair model accounting for diffusional limitations on termination, activation, and deactivation is developed for the mechanoATRP of methyl acrylate. Comparative study by using different diffusion mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…Compared with photomediation, the ultrasound-generated free radicals based on piezocatalysts are usually formed uniformly throughout the reaction system, avoiding the concentration gradients caused by the attenuation of light penetration . Specifically, piezoelectric ZnO nanoparticles (NPs) and barium titanate (BTO) NPs , are able to achieve a mechanically induced electron transfer process and promote the mechano-induced polymerization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with photomediation, the ultrasound-generated free radicals based on piezocatalysts are usually formed uniformly throughout the reaction system, avoiding the concentration gradients caused by the attenuation of light penetration . Specifically, piezoelectric ZnO nanoparticles (NPs) and barium titanate (BTO) NPs , are able to achieve a mechanically induced electron transfer process and promote the mechano-induced polymerization.…”
mentioning
confidence: 99%
“… Although the conversion of MA catalyzed by ZnO can reach 70% in the previous work, it required longer reaction time (8 h) and stronger ultrasonic power (70 W) . For the BTO system, the conversion can reach 91% in 6 h, but more stringent conditions are required (100 W, 50 °C). The results indicated that this ZnO NRs-based system has significant advantages in monomer conversion, loading of piezocatalysts, reaction time, reaction temperature, ultrasonic power, and other aspects.…”
mentioning
confidence: 99%
“…in which D com p,i is the center-of-mass diffusion coefficient for a macromolecule of chain length i, which in practice is considered equal to its counterpart describing the segmental contribution, 86 and D com m is the center-of-mass coefficient for the corresponding monomer, as accessible via the free volume theory (FVT [69][70][71][72] ) as highlighted in ESI. † (3) Upon inputting the scaled diffusion coefficients (eqn (2)), a (FVT-based) parallel encounter pair model 23,[69][70][71][72]87 can be used to obtain the individual apparent rate coefficients that replace pure chemical or intrinsic ones. For example, for (irreversible) termination between radicals of chain length i and j this first diffusion model implementation implies that:…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…With the development of computer simulation, kinetic models have been widely used in modeling chain-growth polymerization such as free radical polymerization, [21][22][23][24][25][26][27] free radical-induced grafting and cross-linking, [28][29][30][31][32][33] and step-growth polymerization. [34][35][36][37] Unfortunately, few broadly applicable kinetic models to reveal competitive hybrid independent mechanisms are available in IPN synthesis.…”
Section: Introductionmentioning
confidence: 99%